Evidence of Early Alterations in Adipose Tissue Biology and Function and Its Association With Obesity-Related Inflammation and Insulin Resistance in Children - Kathrin Landgraf; Denise Rockstroh; Isabel Viola Wagner; Sebastian Weise; Roy Tauscher; Julian Tristan Schwartze; Dennis Löffler; U. Bühligen; Magdalena Wojan; Holger Till; Jürgen Kratzsch; Wieland Kieß; et al. (2014)
Accumulation of fat mass in obesity may result from hypertrophy and/or hyperplasia and is frequently associated with adipose tissue (AT) dysfunction in adults. Here we assessed early alterations in AT biology and function by comprehensive experimental and clinical characterization of 171 AT samples from lean and obese children aged 0 to 18 years. We show an increase in adipocyte size and number in obese compared with lean children beginning in early childhood. These alterations in AT composition in obese children were accompanied by decreased basal lipolytic activity and significantly enhanced stromal vascular cell proliferation in vitro, potentially underlying the hypertrophy and hyperplasia seen in obese children, respectively. Furthermore, macrophage infiltration, including the formation of crown-like structures, was increased in AT of obese children from 6 years on and was associated with higher hs-CRP serum levels. Clinically, adipocyte hypertrophy was not only associated with leptin serum levels but was highly and independently correlated with HOMA-IR as a marker of insulin resistance in children. In summary, we show that adipocyte hypertrophy is linked to increased inflammation in AT in obese children, thereby providing evidence that obesity-associated AT dysfunction develops in early childhood and is related to insulin resistance.